Elasticsearch server : a practical guide to building fast, scalable, and flexible search solutions with clear and easy-to-understand examples /: a practical guide to building fast, scalable, and flexible search solutions with clear and easy-to-understand examples. (2014) - Kuć, Rafał; Rogoziński, Marek
No abstract available